2010
DOI: 10.1113/jphysiol.2010.191098
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide inhibits angiotensin II‐stimulated proliferation in fetal cardiomyocytes

Abstract: The role of atrial natriuretic peptide (ANP) in regulating fetal cardiac growth is poorly understood. Angiotensin II (Ang II) stimulates proliferation in fetal sheep cardiomyocytes when growth is dependent on the activity of the mitogen-activated protein kinase (MAPK) and phosphoinositol-3-kinase (PI3K) pathways. We hypothesized that ANP would suppress near-term fetal cardiomyocyte proliferation in vitro and inhibit both the MAPK and PI3K pathways. Forty-eight hour 5-bromodeoxyuridine (BrdU) uptake (used as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…When the concentration of natriuretic peptides increases, Npr1 and Npr2 activation and cGMP/PKG signaling overtake the actions of Npr3. The inhibitory role of natriuretic peptides on cardiomyocyte proliferation through a cGMP-mediated pathway is supported by previous work in fetal sheep cardiomyocytes (O'Tierney et al, 2010). In vivo cell typerestricted elimination of Npr3 will help further define its role in cardiomyocyte proliferation by disassociating the cell-specific effects of this receptor (adenylyl cyclase inhibition) from its role as a modulator of systemic natriuretic peptide levels (clearance role).…”
Section: Research Articlementioning
confidence: 54%
“…When the concentration of natriuretic peptides increases, Npr1 and Npr2 activation and cGMP/PKG signaling overtake the actions of Npr3. The inhibitory role of natriuretic peptides on cardiomyocyte proliferation through a cGMP-mediated pathway is supported by previous work in fetal sheep cardiomyocytes (O'Tierney et al, 2010). In vivo cell typerestricted elimination of Npr3 will help further define its role in cardiomyocyte proliferation by disassociating the cell-specific effects of this receptor (adenylyl cyclase inhibition) from its role as a modulator of systemic natriuretic peptide levels (clearance role).…”
Section: Research Articlementioning
confidence: 54%
“…In contrast, addition of human/ porcine ANP to fetal sheep cardiomyocytes was shown to inhibit angiotensin II-induced proliferation (32). These studies indicate that the biological effects of ANP are cell type specific and may depend on the NPR subtypes expressed in a given cell type.…”
Section: C566mentioning
confidence: 81%
“…ANP high expression zones are associated with a low mitotic index in the E11.5 ventricles. Previous studies showed that ANP/cGMP signaling could either increase proliferation or decrease proliferation of embryonic/fetal cardiomyocytes from the avian or ovine heart, respectively (23,32). The effects of ANP on proliferation of either CPCs or cardiomyocytes from earlier developmental stages have not yet been determined.…”
Section: E115 Ventricular Cells and Gets Cleaved Into Its Biologicalmentioning
confidence: 99%
See 2 more Smart Citations